Expert Assessment of a Ratio of Expenses at Construction of Oil Transport Infrastructure in the Arctic - A. G. Tutygin; V. B. Korobov; M. H. Gubaidullin; L. A. Chizhova (Управленческое консультирование, 2019)
When assessing the cost of construction and operation of transport infrastructure in the early stages of the investment process, there is a problem in the formalization of some indicators of the factors inﬂuencing decision-making. The temporary impossibility to express them in monetary or comparable natural quantities leads to uncertainty in the ratio between these two groups of factors. On the example of one of the discussed objects of oil transport infrastructure in the territory of the Russian Arctic, quantitative estimates of such uncertainties are obtained, the value of which was very weighty and variable depending on the considered alternative. The authors propose an approach based on the vector representation of factors, fuzzy set theory and expert estimates, which allows developing a criterion of the limit value of uncertainty, allowing making management decisions in the problems of choice. The corresponding model giving the possibility of calculation of such criterion is constructed.